To Remember and Forget: Reconstructing the Imaginary Reality of the Nationalism of Former East Timorese Refugees in Sukabitete, East Nusa Tenggara - Soehadha, Moh (JSW (Jurnal Sosiologi Walisongo), 2024)
The release of the Province of East Timor from Indonesia in 1999 resulted in the displacement of East Timorese from the East Timor region to several provinces in Indonesia. Some refugees remained in Indonesia and chose to become Indonesian citizens. As new citizens, the former East Timor refugees experienced a struggle to foster a sense of nationalism toward Indonesia. This article originates from the results of qualitative reflective research using literature data and archival notes from former East Timor refugees, which were analyzed using ethnographic content analysis and rhetorical analysis methods. The study concludes that memories of past life in East Timor and the present reality of life in ex-refugee settlements in Indonesia generate diverse imaginations about Indonesia. To build a sense of nationality, the former East Timorese refugees must reconstruct their imaginations about Indonesia based on the past and present realities they have experienced, which are not all imaginary.